ANALYZING THE RELATIONSHIP BETWEEN PROFITABILITY AND CAPITAL STRUCTURE OF COMPANIES IN THE INTRODUCTION AND MATURE PHASES - Hanna Wijaya; Rita Juliana (UNKLAB Business School, 2023)
Numerous empirical studies have consistently highlighted a significant inverse correlation between a firm's profitability and its choice of capital structure, aligning with the pecking-order theory, primarily attributed to information asymmetry dynamics. Cooney & Kalay (1993) extended this theory with the concept of a generalized pecking order, elucidating a shift in the theory's relevance when information asymmetry is influenced more by uncertainties related to growth rather than asset composition. This study employs the two-phase company cycle framework introduced by (Dickinson, 2011), distinguishing between the introductory and maturity phases, which are known to exhibit distinct patterns of information asymmetry. Through empirical analysis, we evaluate the applicability of the pecking-order theory in explaining the interplay between profitability and capital structure, incorporating the notion of a generalized pecking order. Our research findings underscore that the pecking-order theory holds limited relevance during the introductory phase but gains significance during the maturity phase, particularly in elucidating the relationship between profitability and capital structure. During the introductory phase, we observed a positive association between profitability and debt issuance, while profitability exhibited a negative association with equity issuance. Keywords: Capital Structure, Firm life cycle, Information Asymmetry, Pecking Order, Profitability Banyak studi empiris telah secara konsisten menyoroti hubungan terbalik yang signifikan antara profitabilitas perusahaan dan pilihan struktur modalnya, sesuai dengan teori pecking-order, yang utamanya disebabkan oleh dinamika asimetri informasi. Cooney & Kalay (1993) memperluas teori ini dengan konsep pecking order yang umum, mengungkapkan pergeseran dalam relevansi teori tersebut ketika asimetri informasi lebih dipengaruhi oleh ketidakpastian pertumbuhan daripada komposisi aset. Studi ini menggunakan kerangka kerja siklus perusahaan dua tahap yang diperkenalkan oleh Dickinson (2011), membedakan antara fase pengenalan dan kematangan, yang dikenal memiliki pola asimetri informasi yang berbeda. Melalui analisis empiris, kami mengevaluasi aplikabilitas teori pecking-order dalam menjelaskan hubungan antara profitabilitas dan struktur modal, dengan menggabungkan gagasan pecking order yang umum. Temuan penelitian kami menekankan bahwa teori pecking-order memiliki relevansi terbatas selama fase pengenalan tetapi menjadi lebih signifikan selama fase kematangan, terutama dalam menjelaskan hubungan antara profitabilitas dan struktur modal. Selama fase pengenalan, kami mengamati hubungan positif antara profitabilitas dan penerbitan utang, sementara profitabilitas menunjukkan hubungan negatif dengan penerbitan ekuitas. Kata kunci: Struktur Modal, Siklus Hidup Perusahaan, Informasi Asimetris, Pecking order, Profitabilitas